Implementasi Layanan Bimbingan Konseling dalam Meningkatkan Disiplin dan Motivasi Belajar di SMK Smart Ar-rahman - Rahma Setika; Siti Nurfajriah Abdul Hadi; Ahmad Jauzy Al Faqih; Rahmania Revalina Baruta; Rahma Alfirdaus; Farida, Nur Aini (At-Tathbīq: Journal of Education and Learning, 2025)
This study aims to describe the implementation of guidance and counseling (BK)services at SMART AR-RAHMAN Vocational School and its role in improvingacademic discipline and student learning motivation. The research method usedwas descriptive qualitative, with data collection techniques including observation,semi-structured interviews, and documentation. The results indicate that BKservices at the school are systematically implemented through individualcounseling, group counseling, classical guidance, and information services.Guidance and counseling teachers act as facilitators, motivators, and counselorsusing a humanistic approach that builds trust and maintains confidentiality. Closecollaboration between guidance and counseling teachers and Islamic ReligiousEducation teachers provides comprehensive character development, integratingstudents' psychological and spiritual aspects. Although guidance and counselingservices have a positive impact on discipline and learning motivation, challengesremain in the form of negative stigma among students who associate guidanceand counseling teachers with punishment. Implementing responsivecommunication strategies, understanding the characteristics of Generation Z,and utilizing social media are key solutions to improve the image of guidance andcounseling and enhance service effectiveness. This study recommends improvingsustainable guidance and counseling service planning and strengtheningcollaboration across teachers to support students' holistic development.